Changes in Livelihood after Construction of NamOu 1 Hydropower HuayLo Village, PakOu District, Luang Prabang Province - KEOMANY, Chitlumphone; MANIVANH , Nouphone; VANAPHON , Anousith; PHETDONMO, Phaivanh (Souphanouvong University Journal Multidisciplinary Research and Development, 2023)
The results of the study found Out that after the construction of NamOu 1 hydroelectric dam, PakOu District, Luang Prabang Province The economic and social condition of the people of HuayLo village before the relocation of the village and after the relocation of the village, caused changes in many aspects and the first thing that makes us aware of these changes is from the study and research on the structure and structure of the economy within the village including the property of the people in the village. In addition, there are also changes in the nature of land use for production, production patterns have changed from before 2016 and after 2022. to raise animals, the people received promotion funds from the NamOu Hydropower Project in the amount of 10,000,000 kip per family. Another change is the characteristics of one-story houses, two-story houses and modern houses before 2016 and 2022 will see more changes including property and household appliances. Satisfaction (1) Benefits have a high level of satisfaction with an average value of 3.70, (2) Regulatory satisfaction has a high level of satisfaction with an average value of 3.64 (3) Conservation satisfaction has a moderate level of satisfaction with an average value of 3.50. (4) Satisfaction with infrastructure has a high level of satisfaction with an average value of 3.85.